Beyond Likes and Shares: Unveiling the Sequential Mediation of Brand Equity, Loyalty, Image, and Awareness in Social Media Marketing's Influence on Repurchase Intentions for High-Tech Products. - K Laveen Kumar; S Anjani Devi (Qubahan Academic Journal)
This study aims to investigate the impact of social media marketing activities (SMMA) on repurchase intention (RPI) with the mediating effect of brand equity (BE), Brand loyalty (BL), Brand image (BI), and Brand awareness (BA) on high-tech products. This study utilized a purposive sampling technique. The data were collected through a structured questionnaire technique from 385 consumers. The descriptive data analysis through SPSS and hypothesis testing through SMART PLS (3.330). The results demonstrate that SMMA positively influences RPI. Additionally, BL, BA, and BI positively mediate the relationship between the SMMA and RPI. Finally, BE negatively mediates the relationship between SMMA and RPI. In theory, it enhances our comprehension of the mechanisms by which SMM impacts consumer behaviour, illuminating the intermediate functions of brand-related notions. In essence, the results provide useful information for marketers who want to use social media platforms efficiently to increase the likelihood of customers buying high-tech products again.